2015
DOI: 10.1074/jbc.m115.644781
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Architecture of the Infectious Salmon Anemia Virus (ISAV) Core Fusion Protein Illustrates a Carboxyl-Carboxylate pH Sensor

Abstract: Background:The infectious salmon anemia virus (ISAV) fusion (F) protein displays pH-dependent host fusion activity. Results: Thermal stability of ISAV F is inversely correlated with pH. Conclusion: ISAV F exhibits class I viral fusion architecture that is stabilized at fusion pH by carboxyl-carboxylate electrostatics. Significance: This analysis contributes new model principles to our understanding of the diversity of viral entry strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Traversing the endosomal pathway introduces the dissociated ISAV F protein to a steady decrease in pH, which is the final, irreversible signal for ISAV F protein rearrangement, consistent with previous studies that ISAV F is stabilized in its postfusion conformation at low pH (30). Interestingly, the expression of ISAV F on the surface of cultured cells is sufficient for syncytia formation when these cells are exposed to low-pH media (31).…”
Section: -Oassupporting
confidence: 89%
“…Traversing the endosomal pathway introduces the dissociated ISAV F protein to a steady decrease in pH, which is the final, irreversible signal for ISAV F protein rearrangement, consistent with previous studies that ISAV F is stabilized in its postfusion conformation at low pH (30). Interestingly, the expression of ISAV F on the surface of cultured cells is sufficient for syncytia formation when these cells are exposed to low-pH media (31).…”
Section: -Oassupporting
confidence: 89%
“…In other viruses, this stimulus induces major F protein structural rearrangements and the assembly of the head-domain heptad repeats into a central, trimeric α-helical coiled coil structure that propel the fusion peptide towards the target membrane [84,98]. Recent structural analysis confirmed that in ISAV F protein, residues E327 and E329 carboxyl-carbonate acts as a pH sensor that once activated at low pH binds and stabilises the extended central coiled-coil region via strong short hydrogen bonds [45]. In the present study, both the full length and deleted HPR HE could potentially allow the proteolytic cleavage to take place.…”
Section: Discussionmentioning
confidence: 99%
“…The ISAV F is a pH-dependent class I membrane fusion protein which needs cleavage by a host proteolytic enzyme for activation [9,45]. The F protein is generated as a 50 kDa inactive precursor molecule (F0), which once cleaved results in two disulphide linked subunits, F1 and F2 at 30 and 20 kDa respectively [9].…”
Section: Introductionmentioning
confidence: 99%
“…As expected, ISAV M1 is expressed late during infection and accumulates in both nucleus and cytosol (25,26). A number of findings indicate that the overall organization of the ISA virion, including the viral RNP (27), the nucleoprotein (28), and the viral fusion machinery (29), shares a high level of structural homology to those of the influenza viruses.…”
mentioning
confidence: 88%